Medicinal use of ferns: an ethnobotanical review - Mazhani Muhammad,; Zitty Sarah Ismail,; Schneider, Harald; Hawkins, Julie A. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Many fern (monilophyte) species are used in traditional medicine by indigenous communities and described in folklore in many parts of the world. Numerous plants used in folk remedies are considered efficacious by today’s standards and some have been accepted as main sources of drug discovery. However, the modern use of ferns in medicine, as for other lower plants, is neglected and thought to be only of minor and local significance. In this study, we provide a comprehensive, global summary of the ethnomedicinal uses of ferns. Based on these data, the documented therapeutic potential of ferns is analysed to highlight the gaps in our knowledge that deserve further investigation and can also be used as a starting point in the development of new drugs. Literature reports of ethnomedicinal uses of ferns were collated based on published work from scientific journals, books, reports, and online databases. A total of 442 species are reported to be used, and the most prevalent therapeutic applications are for gastrointestinal disorders (45% of species). The species most frequently cited are Adiantum capillus-veneris L., Equisetum arvense L. and Equisetum ramosissimum ssp. ramosissimum Desf. Each of these important species has been reported in the primary literature more than 60 times. Further research targeting the individual ingredients responsible for the pharmacological effects and their mechanisms of action is needed. These studies will further support the therapeutic potential of medicinal fern species for their future clinical applications in modern medicine.